Leveraging customer knowledge to enhance process innovation: Moderating effects from market dynamics. Issue 2 (12th July 2018) - Nguyen, Hung; Harrison, Norma
Abstract : Purpose: Nowadays, companies compete and win based on the capabilities they can leverage across their supply chains. With unpredictable and turbulent business environment, supply chains are seeking to customer knowledge as sources of competitive advantage. The purpose of this paper is to empirically test a conceptual framework to investigate the roles of customer leverage (CL) on process innovation and the relationships to performance. Design/methodology/approach: Drawing upon the knowledge-based view, this study argues that CL is the sources of firms' process innovation. This study also posits that process innovation mediates the relationship between CL and performance based on transaction cost economics. This empirical study employed 650 manufacturers across different regions. Findings: This study showed that strong association exists between a manufacturing firm's CL capability and its process innovation and performances. Process innovation play critical mediating roles in absorbing and transforming customer knowledge in supply chains. In a more dynamic market, CL strengthens the positive impacts on process innovation. Research limitations/implications: This study further highlights the need to emphasize both strategic and CL capability in dynamic environments as these may be needed to enable the firm to seize market niches that may open up in such environments. Similarly, managers should emphasize CL capability and process changes in competitive environments as they are more difficult to imitate from competitors in regards of new product or services. Practical implications: These results extend the limited existing research on global manufacturing context that the customer knowledge are effective sources for increasing innovative processes. The higher the market turbulence, the stronger the pressures for CL demanded by process innovation. The findings also confirm that process innovation plays a mediating role in absorbing and transforming customer knowledge in improving costs and financial measures. This is an important result that highlights the mechanism by which customer knowledge can influence a firm's bottom line. Originality/value: This study examined the linkages between a marketing concept and operations and supply chain management.